Serine Threonine Kinase Receptor‐Associated Protein Deficiency Impairs Mouse Embryonic Stem Cells Lineage Commitment Through CYP26A1‐Mediated Retinoic Acid Homeostasis. (17th July 2018) - Jin, Lin; Chang, Chenbei; Pawlik, Kevin M.; Datta, Arunima; Johnson, Larry M.; Vu, Trung; Napoli, Joseph L.; Datta, Pran K.
Abstract: Retinoic acid (RA) signaling is essential for the differentiation of embryonic stem cells (ESCs) and vertebrate development. RA biosynthesis and metabolism are controlled by a series of enzymes, but the molecular regulators of these enzymes remain largely obscure. In this study, we investigated the functional role of the WD‐domain protein STRAP (serine threonine kinase receptor‐associated protein) in the pluripotency and lineage commitment of murine ESCs. We generated Strap knockout (KO) mouse ESCs and subjected them to spontaneous differentiation. We observed that, despite the unchanged characteristics of ESCs, Strap KO ESCs exhibited defects for lineage differentiation. Signature gene expression analyses revealed that Strap deletion attenuated intracellular RA signaling in embryoid bodies (EBs), and exogenous RA significantly rescued this deficiency. Moreover, loss of Strap selectively induced Cyp26A1 expression in mouse EBs, suggesting a potential role of STRAP in RA signaling. Mechanistically, we identified putative Krüppel‐like factor 9 (KLF9) binding motifs to be critical in the enhancement of non‐canonical RA‐induced transactivation of Cyp26A1. Increased KLF9 expression in the absence of STRAP is partially responsible for Cyp26A1 induction. Interestingly, STRAP knockdown in Xenopus embryos influenced anterior‐posterior neural patterning and impaired the body axis and eye development during early Xenopus embryogenesis. Taken together, our study reveals an intrinsic role for STRAP in the regulation of RA signaling and provides new molecular insights for ESC fate determination. Stem Cells 2018;36:1368–1379 Abstract : Schematic model of serine threonine kinase receptor‐associated protein (STRAP)‐mediated mouse embryonic stem cell differentiation. STRAP is required for stem cell lineage commitment through retinoic acid (RA) signaling. A balanced RA signaling is mediated, at least in part, by the Cyp26A1 expression. Overexpressed KLF9 enhances Cyp26A1 promoter activity and accounts for the high Cyp26A1 expression in Strap KO cells. In contrast, reduced expression of KLF9 in Strap WT cells would result in the low CYP26A1 expression and activated RA signaling.